The Impact of Banking Capital Components of Balance of Payments on Economic Growth of India: An examination of the impact of balance of payments indicators on the economic growth of India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study intends to examine the performance of balance of trade and analyze status of the indicators of balance of payments of Indian economy. The data has been collected for last 10 years (2005-2015) and from the secondary sources. The findings conclude that the balance of trade and balance of payments are the important components of Indian economy and these are moving in positive direction.